Social Protection in Indonesia: Reforming Opportunities during Covid-19 Pandemic - Sumadi, Pungky (Asean Social Work Journal, 2023)
Indonesia’s social protection system provides programs covering its population according to a life cycle approach. The programs have been used as a means to address the social implications of locking down policy due to the COVID-19 pandemic.This paper aims to describe how Indonesia is reforming its social protection agenda.This article used a literature review for data gathering in describing the overall social protection reform agenda. It also used surveys in 198 pilot villages to try out three social protection policy instruments: a socio-economic registry, a digitalized village monograph, and an integrated approach to zero extreme poverty intervention.To deal with the social implications of locking down policy, Indonesia made use of the existing and ongoing programs, and also adding some new ones, even though the modality is no different: cash transfer. Various operational problems emerged during the implementation. The data accuracy of the existing beneficiary rosters is getting worse and unreliable. Different rosters produced by different ministries only create confusion in program implementation. A socio-economic registry is a potential solution for integrating beneficiary rosters produced individually by different ministries. Additionally, a lack of coordination among key ministries in social protection programs tends to provide one policy fit for all; leaving behind the role of local governments and different local needs. Having understood the situation, President Jokowi is determined to achieve the zero extreme poverty target by 2024 by reforming the country’s social protection policy.